Basic Operation Principles and Control Algorithm for a High-pressure Membrane-less Electrolyser - Solovei, V.V.; Kotenko, A.L.; Vorobiova, I.O.; Shevchenko, A.A.; Zipunnikov, M.M. (Проблеми машинобудування, 2018)
A technology of the cyclic generation of hydrogen and high-pressure oxygen, implemented in a single-module and multi-module electrolysis installation, is considered. A schematic operation diagram for implementing the method with four series-connected modules is given. Розглянуто технологію циклічного генерування водню та кисню високого тиску, що реалізується в одномодульній і багатомодульній електролізній установці. Наведено принципову схему її роботи для реалізації способу із чотирма послідовно підключеними модулями. Рассмотрена технология циклического генерирования водорода и кислорода высокого давления, реализуемая в одномодульной и многомодульной электролизной установке. Приведена принципиальная схема ее работы для реализации способа с четырьмя последовательно подключенными модулями.